Dimensions for argument and variability in child protection decision-making. Issue 2 (3rd April 2018) - Mosteiro, A.; Beloki, U.; Sobremonte, E.; Rodríguez, A.
ABSTRACT: The purpose of this article is to analyse the arguments presented by 181 professionals in the child protection system of the Basque Country (Spain) to justify their decisions regarding the implementation of measures related to family preservation or separation. The implementation of a case vignette demonstrated variability in professional decision-making, with 62% of professionals choosing family preservation and 38% opting for family separation. A series of argument categories which can be used by most professionals when making decisions are extracted from analysis of the content. However, in spite of using similar types of arguments, the professionals differed in the importance they attributed to such criteria and their interpretations. Differences in decision thresholds were directly related to professionals' beliefs regarding the benefits of the interventions analysed. To reduce this variability, reflecting on these beliefs and analysing the effectiveness of interventions in child protection to incorporate evidence of professional judgement are recommended. The present study, on the one hand, identifies the argument categories used to justify decisions and, on the other, analyses the existing variability when interpreting these categories.